PENGARUH MODAL USAHA, TENAGA KERJA, DAN HARGA JUAL, TERHADAP TINGKAT PENDAPATAN USAHA TENUN IKAT (Studi Empiris Pada Pelaku Usaha Tenun Ikat Di Kelurahan Nangalimang Kecamatan Alok Kabupaten Sikka) - Margaretha Avitha Sarly; Wihelmina Mitan; Paulus Libu Lamawitak (Jurnal Projemen UNIPA, 2025)
This research aimed to examine how business capital, labor, and selling price affect the income of ikat weaving enterprises, using a case study of weaving entrepreneurs in Nangalimang, Alok Sub-district, Sikka Regency. This research investigated causal linkages using a quantitative technique with an associative design. The population consisted of ikat weaving entrepreneurs in Nangalimang, and a sample of 40 respondents was chosen for data collection. The primary instrument was a questionnaire, and the responses were analysed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS). The results indicated that enterprise income was significantly positively impacted by business capital, whereas labor and selling price did not exhibit any significant influence. However, when considered concurrently, firm capital, labor, and selling price had a major impact on income levels.